The Influence of Macroeconomic and Socio-Economic Factors on The Achievement of SDG 10 in Java - Miranda, Mira (Yayasan Meira Visi Persada, 2025)
This study investigates the relationship between macroeconomic variables and income inequality on the island of Java using the panel regression method. Panel regression analysis shows that inflation, GRDP, decline and exchange rate influence income inequality on Java Island simultaneously. Partially, it shows that inflation, GRDP, poverty and the exchange rate have a significant effect.